Mealworm (Tenebrio molitor) oil characterization and optimization of the free fatty acid pretreatment via acid-catalyzed esterification. (1st September 2021) - Siow, Hao Sen; Sudesh, Kumar; Murugan, Paramasivam; Ganesan, Shangeetha
Graphical abstract: Highlights: Mealworm oil has higher ratio of unsaturated fatty acids than saturated fatty acids. Mealworm oil is a promising feedstock for oil-based products. Mealworm oil is pretreated for FFA reduction via acid-catalyzed esterification. Four independents factors varied to study the effects on the conversion of FFA. Conversion of FFA are optimized using response surface methodology. Abstract: The physical and chemical properties of mealworm ( Tenebrio molitor ) oil were studied. Mealworm powder has a high oil content of 37.54 ± 0.78% with a high free fatty acid (FFA) content of 10.84 ± 0.005%. The primary fatty acids of mealworm oil were oleic acid (30.37%), linoleic acid (25.07%) and palmitic acid (19.54%). The mealworm oil decomposed almost completely after 470 °C. An optimization study of acid-catalyzed esterification using response surface methodology (RSM) was conducted to reduce the high level of FFA content to a range below 1% to be suitably used for biodiesel production via alkali-catalyzed transesterification. The optimum parameters were 5.8% w/w sulfuric acid as catalyst, 24:1 methanol to oil ratio, 174 min reaction time at a temperature of 74 °C. The methyl esters conversion obtained using these optimum condition parameters was 92.74 ± 0.92% indicating FFA content was successfully lowered to less than 1%, which is favorable for alkali-catalyzed transesterification to take place and convert the triglycerides in the oil into biodiesel. The pretreated oil is then converted to biodiesel and the properties were found to meet the ASTM D6751 standards.